The relative risk of aortic aneurysm in patients with giant cell arteritis compared with the general population of the UK - Robson, J; Kiran, A; Maskell, J; Hutchings, A; Arden, N; Dasgupta, B; Hamilton, W; Emin, A; Culliford, D; Luqmani, R (2015)
Objectives: To evaluate the risk of aortic aneurysm in patients with giant cell arteritis (GCA) compared with age-, gender- and location-matched controls.Methods: A UK General Practice Research Database (GPRD) parallel cohort study of 6999 patients with GCA and 41 994 controls, matched on location, age and gender, was carried out. A competing risk model using aortic aneurysm as the primary outcome and non-aortic-aneurysm-related death as the competing risk was used to determine the relative risk (subhazard ratio) between non-GCA and GCA subjects, after adjustment for cardiovascular risk factors.Results: Comparing the GCA cohort with the non-GCA cohort, the adjusted subhazard ratio (95% CI) for aortic aneurysm was 1.92 (1.52 to 2.41). Significant predictors of aortic aneurysm were being an ex-smoker (2.64 (2.03 to 3.43)) or a current smoker (3.37 (2.61 to 4.37)), previously taking antihypertensive drugs (1.57 (1.23 to 2.01)) and a history of diabetes (0.32 (0.19 to 0.56)) or cardiovascular disease (1.98 (1.50 to 2.63)). In a multivariate model of the GCA cohort, male gender (2.10 (1.38 to 3.19)), ex-smoker (2.20 (1.22 to 3.98)), current smoker (3.79 (2.20 to 6.53)), previous antihypertensive drugs (1.62 (1.00 to 2.61)) and diabetes (0.19 (0.05 to 0.77)) were significant predictors of aortic aneurysm.Conclusions: Patients with GCA have a twofold increased risk of aortic aneurysm, and this should be considered within the range of other risk factors including male gender, age and smoking. A separate screening programme is not indicated. The protective effect of diabetes in the development of aortic aneurysms in patients with GCA is also demonstrated.